Assessing Dentists’ knowledge and training needs in smoking cessation and Electronic Nicotine Delivery Systems: a cross-sectional study in Kosovo - Zana Sllamniku Dalipi; Mirlinda Sopi Krasniqi; Donika Bajrami Shabani; Linda Dula (Brazilian Dental Science)
Background: Electronic cigarettes (e-cigarettes) vaporize a liquid solution containing nicotine and are marketed as safer than traditional tobacco. However, they are linked to health issues, including cardiovascular, respiratory, and oral problems. Dental professionals play a key role in educating patients and supporting smoking cessation. Objective: This study evaluates dentists’ knowledge of smoking cessation methods in Kosovo and identifies the need for further training. Material and Methods: The study involved 189 licensed dentists in Kosovo, using an 18-question questionnaire to assess their discussions about e-cigarettes, smoking cessation knowledge, and training participation. Data were analyzed using SPSS 22. Results: Among participants, 42.9% were male and 57.1% female. Most (63.0%) felt confident discussing e-cigarettes’ harmful effects, while only 36.5% were knowledgeable about advanced cessation methods, and 11.6% were familiar with structured intervention models like the 5As and 5Rs. Participation in training was low (27.0%). Dentists showed confidence in discussing e-cigarettes but lacked knowledge of advanced cessation methods. This gap highlights the need for standardized educational programs to improve counseling effectiveness. Conclusion: While dentists in Kosovo recognize the risks of e-cigarettes, there is a clear need for enhanced training in smoking cessation methods to better support patients.